2018
DOI: 10.3166/rfg.2018.00240
|View full text |Cite
|
Sign up to set email alerts
|

Stimuler l’innovation radicale par l’usage d’un réseau social d’entreprise ?

Abstract: Les innovations radicales peuvent bousculer les positions établies d’entreprises d’industries matures, qui se heurtent à des limites structurelles pour générer elles-mêmes de telles innovations. À partir d’une expérimentation menée au sein du groupe pétrolier Technip, cet article explore la possibilité de mobiliser un réseau social d’entreprise (RSE) pour faciliter les phases amont de l’innovation radicale. Il en ressort que les propriétés des réseaux sociaux d’entreprise facilitent la circulation de connaissa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
2
2
0
Order By: Relevance
“…ESN integrates in majority exchange of explicit knowledge that permits employees to improve their tasks and fuels incremental changes and exploitative innovation. Results are in the same vein of the exploratory research of Dalmasso et al (2018) who emphasized that ESN does not have a direct effect on radical innovation but is a key factor in the fuzzy front-end of radical innovation as it promotes knowledge sharing and the creation of new relations. They claim in this sense that it “do not substitute to the need of intermediation and of an organizational context favorable to radical innovation” (Dalmasso et al , 2018).…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…ESN integrates in majority exchange of explicit knowledge that permits employees to improve their tasks and fuels incremental changes and exploitative innovation. Results are in the same vein of the exploratory research of Dalmasso et al (2018) who emphasized that ESN does not have a direct effect on radical innovation but is a key factor in the fuzzy front-end of radical innovation as it promotes knowledge sharing and the creation of new relations. They claim in this sense that it “do not substitute to the need of intermediation and of an organizational context favorable to radical innovation” (Dalmasso et al , 2018).…”
Section: Discussionsupporting
confidence: 67%
“…Results are in the same vein of the exploratory research of Dalmasso et al (2018) who emphasized that ESN does not have a direct effect on radical innovation but is a key factor in the fuzzy front-end of radical innovation as it promotes knowledge sharing and the creation of new relations. They claim in this sense that it “do not substitute to the need of intermediation and of an organizational context favorable to radical innovation” (Dalmasso et al , 2018). Although findings show that ESN use is not linked significantly to exploratory innovation, it improves indirectly exploratory innovation through its positive effect on HC and SC.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Social networks are considered "collaborative tools" to foster knowledge sharing, boost interactions between organizational and stakeholders and promote innovation (Turban et al, 2011). Also, other studies (Dalmasso et al, 2018;Berraies & Chaher, 2014) found that the use of social networks develops a radical innovation in the companies, by promoting the flow of knowledge and the creation of new relationships. Berraies and Chaher (2014) also stressed that interactions between internal and external actors promote strategic knowledge, particularly: the development of new information and communication technologies, new methods, new suppliers of raw materials and the response to the market or competitive needs.…”
Section: The External Stakeholders' Perspectivementioning
confidence: 99%